Direct and Selective Electrocarboxylation of Styrene Oxides with CO2 for Accessing β‐Hydroxy Acids. (4th August 2022) - Zhang, Ke; Ren, Bai‐Hao; Liu, Xiao‐Fei; Wang, Lin‐Lin; Zhang, Min; Ren, Wei‐Min; Lu, Xiao‐Bing; Zhang, Wen‐Zhen
Abstract: Highly selective and direct electroreductive ring‐opening carboxylation of epoxides with CO2 in an undivided cell is reported. This reaction shows broad substrate scopes within styrene oxides under mild conditions, providing practical and scalable access to important synthetic intermediate β ‐hydroxy acids. Mechanistic studies show that CO2 functions not only as a carboxylative reagent in this reaction but also as a promoter to enable efficient and chemoselective transformation of epoxides under additive‐free electrochemical conditions. Cathodically generated α ‐radical and α ‐carbanion intermediates lead to the regioselective formation of α ‐carboxylation products. Abstract : Highly selective and direct electroreductive ring‐opening carboxylation of epoxides with CO2 in an undivided cell to yield synthetically important β ‐hydroxy acids is described. CO2 functions not only as a carboxylative reagent in this reaction but also as a promoter to enable efficient and chemoselective transformation of epoxides under additive‐free electrochemical conditions.